DIAGNOSTIC MEASURES FOR PULMONARY BLEEDING (World Bulletin of Public Health, 2022)
Pulmonary hemorrhage, being a severe complication of various pathological conditions, requires an integrated approach to diagnosis, treatment and prevention, taking into account the etiology and pathogenesis in specialized departments. Currently, the tactics of treatment of pulmonary hemorrhage consists of the combined use of hemostatic therapy, endoscopic imaging methods, Xray endovascular surgery methods, as well as surgical methods of treatment. The result of treatment of patients with this pathology largely depends on the cause that led to this complication, the caliber of the damaged vessel, the nature and volume of bleeding, timely provision of specialized care. This article provides its own treatment material for 394 patients with this pathology examined and treated in the department of thoracovascular surgery of the Andijan branch of the Republican Scientific Center for Emergency Medical Care from 2015 to 2019.
Keywords: Pulmonary; cardio-thoracic; tuberculosis